Synthesis of azatriquinacene ; and, Backbone modified DNA using transition metal catalysts - De Lera Ruiz, Manuel (2001)
Azatriquinacene (10-Azatricyclo[5.2.1.0"10]deca-2,5,8-triene) and azatriquinadiene (10-Azatricyclo[5.2.1.01"0]deca-2,8-diene) have been synthesised in respectively eight and seven steps from pyrrole. 27 Woodward dimerisation4 of azatriquinacene has beenattempted although no evidence of diazadodecahedraneh as yet been found. A unique nonacyclic species (10-Azatricyclo[5.2.1.0''10]-2,9-bis[1-azatricyclo [5.2.1.01'10]decane]dec-l-eneh) as been obtained by trimerisation of an enamine.Its structure and extraordinarily high basicity (pKa 25.1) make it a new class of "proton sponge". During this study thirteen new substituted azatriquinanes and four new substituted azabicycles have been synthesised, and nine crystal structures have been solved, providing valuable insights into the chemistry and structure of this novel heterocyclic system.